2021
DOI: 10.5194/gmd-14-3437-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the physical and biogeochemical state of the global ocean component of UKESM1 in CMIP6 historical simulations

Abstract: Abstract. The ocean plays a key role in modulating the climate of the Earth system (ES). At the present time it is also a major sink both for the carbon dioxide (CO2) released by human activities and for the excess heat driven by the resulting atmospheric greenhouse effect. Understanding the ocean's role in these processes is critical for model projections of future change and its potential impacts on human societies. A necessary first step in assessing the credibility of such future projections is an evaluati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 124 publications
(165 reference statements)
0
42
0
Order By: Relevance
“…2.4. The biogeochemical performance of NEMO-MEDUSA has previously been extensively validated at low resolution in the studies of Yool et al (2013Yool et al ( , 2021, with traceability at higher resolution demonstrated in Yool et al (2015).…”
Section: Forcing Data and Domainmentioning
confidence: 99%
“…2.4. The biogeochemical performance of NEMO-MEDUSA has previously been extensively validated at low resolution in the studies of Yool et al (2013Yool et al ( , 2021, with traceability at higher resolution demonstrated in Yool et al (2015).…”
Section: Forcing Data and Domainmentioning
confidence: 99%
“…Largely absent from discussions around changing NPP in response to changing nutrient supply is the role of modification to external nutrient inputs to the ocean. While there have been some efforts including dynamic coupling with aerosol nutrient supply at the sea surface (e.g., Yool et al, 2021), future work that accounts for additional external inputs may introduce additional uncertainty in NPP changes. For instance, the inclusion of dynamic Greenland and Antarctic ice sheets in Earth system models is rapidly becoming computationally permissible and the associated changes to freshwater fluxes due to climate change have the potential to influence projections of NPP via both physical and biogeochemical mechanisms (Hopwood et al, 2020).…”
Section: Future Efforts To Reduce Uncertainty In Npp Projectionsmentioning
confidence: 99%
“…For CMIP6, UKESM1.0 with neither interactive ice sheets nor ice shelf cavities in the ocean model was spun up to equilibrium with preindustrial forcing (Yool et al, 2021) before an initial condition ensemble of historical simulations was conducted, starting from different points in the preindustrial control run (Sellar et al 2019). While these historical simulations provided states ready for UKESM1.0 ScenarioMIP projections (Swaminathan et al, 2022), they are not directly usable for the ocean in scenario runs in UKESM1.0-ice, given the absence of ocean under the ice shelves.…”
Section: Standalone Ocean Initialisationmentioning
confidence: 99%